Respiratory diseases. Diagnosis and treatment : educational manual for Master's degree students specialty Medicine - Nazarenko, O. V.; Zemliany, Ya. V.; Назаренко, Олена Валеріївна; Земляний, Ярослав Вадимович (Запорізький державний медико-фармацевтичний університет, 2025)
The educational manual contains materials on the main methods of clinical, laboratory, and instrumental diagnostics, as well as the principles of treatment for the most common diseases of the respiratory system. The textbook is intended for students of medical higher education institutions in preparation for practical classes in the course "Internal Medicine" for the specialty Medicine.